Uncovering the secrets of the Terracotta Warriors: AURORA team’s exciting visit to Xi’an, China - Mohamad, Masilah; Zulkifli, Nordayana; Jamal, Siti Norazura; Mohd Aris, Aslizah; Ibrahim, Aidil; Jaafar, Hasif; Kamaruzaman, Mohd Asyran Safwan; Ong, Wee Chuan (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
The AURORA team’s visit to Xi’an felt like stepping into a living time capsule, surrounded by the breathtaking Terracotta Warriors thousands of uniquely crafted, life-sized soldiers that left everyone in awe. Between admiring the scale and detail of Emperor Qin Shi Huang’s ancient army, mimicking warrior poses, snapping countless photos, and sharing plenty of laughs, the trip blended history, fun, and team bonding. We left with unforgettable memories and a deeper appreciation for the creativity and resilience reflected in this extraordinary archaeological wonder.